A benzimidazole derivative as an effective antitumor agent in terms of syngeneic lung tumors and melanoma treatment - E. F. Komarova; A. S. Morkovnik; O. N. Zhukovskaya; E. V. Verenikina; N. A. Shevchenko; D. V. Khodakova; L. Z. Kurbanova; M. V. Mindar; E. V. Zaikina; A. V. Galina (Южно-Российский онкологический журнал)
Purpose of the study. Evaluation of the effect of the benzimidazole derivative dihydrobromide‑2-(3,4‑dihydroxyphenyl)- 9‑diethylamino-ethylimidazo-[ 1,2‑a] benzimidazole (RU‑185) on the growth of Lewis lung epidermoid carcinoma and B16-F10 melanoma when administered intragastrically.Materials and methods. For the experiment, we used female C57Bl/6j mice, which were inoculated subcutaneously with syngeneic tumors: Lewis lung carcinoma (LLC) and B16-F10 melanoma. RU‑185 was administered intragastrically to animals in a volume of 0.3 ml for 10 days, 1 time per day. For both tumors, depending on single doses of the substance for administration, groups were divided: 1st and 4th – 50 mg/kg, 2nd and 5th – 220 and 3rd and 6th – 500 mg/kg. The control groups were injected intragastrically with physiological saline in the same volumes and according to the same scheme. The following parameters were assessed: tumor volume, increase in life expectancy (T/S, %) and tumor growth inhibition index (TGI, %).Results. For animals with LLC in the 2nd group there is an increase in the indicator of life expectancy (T/S 162.3 %), and in the 3rd group there is a tendency to an increase in the T/S indicator. On the 1st day after the end of treatment in the 2nd and 3rd groups TGI was 73.0 % and 30.1 %, respectively (р < 0.05). On the 7th and 14th days after the end of the use of RU‑185 in the 2nd and 3rd groups the volume of tumors is 3.5 and 1.4 times less (on the 7th day) and 2.3 and 1.3 times (on the 14th day), respectively than in the control group (р < 0.05). At a dose of 220 mg/kg, complete regression of LLC tumors was shown in 20 % of animals.With the growth of B16-F10, the life expectancy of all groups did not differ. Intergroup differences in the dynamics of tumor growth are provided. Highlighted changes were found in the 5th group (on the 14th day after the end of the administration of RU‑185, TGI was 48.7 %).Conclusion. The investigated chemical substance dihydrobromide‑2-(3,4‑dihydroxyphenyl)-9‑diethylamino-ethylimidazo- [1,2‑a] benzimidazole showed antitumor efficacy against syngeneic tumors: Lewis lung epidermoid carcinoma and B16-F10 melanoma when administered intragastrically which leads to further testing of RU‑185 as a potential drug for the treatment of malignant neoplasms.